Pembinaan Warga Gereja Dewasa Menurut Surat Efesus (International Forum of Researchers and Lecturers, 2025)
Ephesians provides important guidance on spiritual and moral formation for adult church members. The main focus of this letter is building maturity in faith through a relationship with Christ, teaching the Word, and community life that reflects the love and unity of the body of Christ. In the context of developing adult church citizens, Ephesians emphasizes the role of the church as a place of growth in faith, unity in the Spirit, and life in love. Messages such as putting on the new self (Ephesians 4:22-24), living in the light (Ephesians 5:8-10), and leadership based on service are at the heart of this formation. Thus, the letter to Ephesians provides a theological and practical framework for nurturing church members to achieve spiritual maturity and grow in harmonious fellowship.